2014
DOI: 10.1038/ncomms5352
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis captures the determinants of the antibiotic cross-resistance interaction network

Abstract: Understanding how evolution of antimicrobial resistance increases resistance to other drugs is a challenge of profound importance. By combining experimental evolution and genome sequencing of 63 laboratory-evolved lines, we charted a map of cross-resistance interactions between antibiotics in Escherichia coli, and explored the driving evolutionary principles. Here, we show that (1) convergent molecular evolution is prevalent across antibiotic treatments, (2) resistance conferring mutations simultaneously enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
267
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(287 citation statements)
references
References 57 publications
14
267
2
4
Order By: Relevance
“…Experimental evolution studies of evolution of antibiotic resistance showed that in many cases resistance-conferring mutations arose both in target and off-pathway genes (5,11). However, mutations conferring resistance against trimethoprim (TMP) were largely limited to the target gene, namely the ORF and upstream region of folA, the gene encoding dihydrofolate reductase (DHFR) (1,5,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evolution studies of evolution of antibiotic resistance showed that in many cases resistance-conferring mutations arose both in target and off-pathway genes (5,11). However, mutations conferring resistance against trimethoprim (TMP) were largely limited to the target gene, namely the ORF and upstream region of folA, the gene encoding dihydrofolate reductase (DHFR) (1,5,11).…”
mentioning
confidence: 99%
“…However, mutations conferring resistance against trimethoprim (TMP) were largely limited to the target gene, namely the ORF and upstream region of folA, the gene encoding dihydrofolate reductase (DHFR) (1,5,11). DHFR is an essential core metabolic enzyme that converts dihydrofolate to tetrahydrofolate-a main source of carbon atoms in several key pathways.…”
mentioning
confidence: 99%
“…Indeed, most pathogenic bacteria become resistant with time to the action of antibiotics. 2,3 This effect represents a paramount medical problem so that new molecules and compounds with high and persistent antibacterial activity are required to face the challenge of emerging infections and the global spread of drug-resistant microbial pathogens. 4 In addition to the treatment of infections, novel preservatives are essential in pharmaceutical and cosmetic areas as an alternative solution to the widely used esters of p-hydroxybenzoic acid (parabens).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of antibiotic resistance under optimized culture conditions and the underlying molecular mechanisms causing the cellular response are well documented (2,(10)(11)(12). The second aim of this study was to investigate whether additional stress factors, such as low pH or increased NaCl concentrations, influence the ability of the cell to acquire antibiotic resistance de novo.…”
mentioning
confidence: 99%